Scalable Realistic Rendering with Many-Light Methods - Dachsbacher, Carsten; Křivánek, Jaroslav; Hašan, Miloš; Arbree, Adam; Walter, Bruce; Novák, Jan (Computer graphics forum, 2014)
Recent years have seen increasing attention and significant progress in many‐light rendering, a class of methods for efficient computation of global illumination. The many‐light formulation offers a unified mathematical framework for the problem reducing the full lighting transport simulation to the calculation of the direct illumination from many virtual light sources. These methods are unrivaled in their scalability: they are able to produce plausible images in a fraction of a second but also converge to the full solution over time. In this state‐of‐the‐art report, we give an easy‐to‐follow, introductory tutorial of the many‐light theory; provide a comprehensive, unified survey of the topic with a comparison of the main algorithms; discuss limitations regarding materials and light transport phenomena and present a vision to motivate and guide future research. We will cover both the fundamental concepts as well as improvements, extensions and applications of many‐light rendering. Recent years have seen increasing attention and significant progress in many‐light rendering, a class of methods for efficient computation of global illumination. The many‐light formulation offers a unified mathematical framework for the problem reducing the full lighting transport simulation to the calculation of the direct illumination from many virtual light sources. These methods are unrivaled in their scalability: they are able to produce plausible images in a fraction of a second but also converge to the full solution over time. In this state‐of‐the‐art report, we give an easy‐to‐follow, introductory tutorial of the many‐light theory.